‘Maternal request’ caesarean sections and medical necessity - Brown, R; Mulligan, A (SAGE Publications, 2023)
Currently, many women who are expecting to give birth have no option but to attempt vaginal delivery, since access to elective planned caesarean sections (PCS) in the absence of what is deemed to constitute ‘clinical need’ is variable. In this paper, we argue that PCS should be routinely offered to women who are expecting to give birth, and that the risks and benefits of PCS as compared with planned vaginal delivery should be discussed with them. Currently, discussions of elective PCS arise in the context of what are called ‘Maternal Request Caesarean Sections’ (MRCS) and there is a good deal of support for the position that women who request PCS without clinical indication should be provided with them. Our argument goes further than support for acceding to requests for MRCS: we submit that healthcare practitioners caring for women with uncomplicated pregnancies have a positive duty to inform them of the option of PCS as opposed to assuming vaginal delivery as a default, and to provide (or arrange for the provision of) PCS if that is the woman's preferred manner of delivery.